Determination of Acute and Active Amoebic Liver Abscess - Ahmed, Sharnali (Universiti Sains Malaysia, 2015)
Amoebic liver abscess (ALA) is a deadly infection caused by the protozoa Entamoeba histolytica. At Hospital Universiti Sains Malaysia, diagnosis of ALA includes antibody detection using a commercial kit based on crude soluble antigens (CSA) of Entamoeba histolytica. However, this method may only be useful in non-endemic area and often cannot differentiate current and past infection when used in endemic areas. DNA-based techniques such as real-time PCR has been utilised to detect E. histolytica DNA of liver biopsy samples with high sensitivity and specificity, but the cost to perform this technique is high and can only be performed in laboratories where specialised equipment and trained personnel are available. This study aimed to identify acute and active infection of ALA by utilising crude soluble antigen (CSA) of E. histotyica to detect IgM and IgG4 respectively in ALA serum samples detected with the commercial IHA kit which detects total IgG. In this experiment, three types of enzyme-linked immunosorbent assay (ELISA) were developed, namely CSA-IgG ELISA, CSA-IgG4 ELISA and CSA-lgM ELISA. The ELlSAs were successfully developed based on optimisation of parameters such as CSA concentration, first antibody (IgG, IgG4 dan IgM) and secondary antibody (anti-IgG, anti-IgG4 dan anti-IgM). The sensitivity of each ELISA was compared with the 30 positive ALA serum samples and 30 negative ALA serum samples that were confirmed by IHA. CSA-IgG ELISA showed a sensitivity and specificity of 96.7%; CSA-IgG4 ELISA revealed a sensitivity and specificity rates of 83.3% dan 90.0% respectively; and CSA-lgM ELISA were found to be 70.0% specific and 50.0% sensitive. In conclusion, this study revealed that 50.0% of the IHA confirmed ALA cases were probably acutely infected; and 83.3% of the confirmed ALA cases were probably active ALA cases.